Muscle Ageing and Sarcopenia Study (MASS) Lifecourse: a valuable resource for understanding skeletal muscle ageing - Rachel Cooper; Christopher Hurst; Holly Syddall; Helen Atkinson; Jonathan G. Bunn; Daniela Carpinelli; Antoneta Granic; Susan J. Hillman; Emma Grace Lewis; Claire McDonald; Katie Sloan; Karen Suetterlin; et al. (GeroScience, 2026)

Decommodifying cacao: matchmaking between producers and buyers of fine flavour cacao from Peru - Evert Thomas; Gesabel Villar; Diego Zavaleta; Viviana Ceccarelli; Fredy Yovera; Trent Blare; Marleni Ramirez; Christoph Oberlack; Rachel Atkinson (Ecological Economics, 2026)

The distribution of cadmium in soil and cacao beans in Peru - Evert Thomas; Rachel Atkinson; Diego Zavaleta; Carlos Rodriguez; Sphyros Lastra; Fredy Yovera; Karina Arango; Abel Pezo; Javier Aguilar; Miriam Tames; Ana Ramos; Wilbert Cruz; et al. (Science of The Total Environment, 2023)

Identifying the origin of acrylamide in Peruvian panela production to inform strategies for its reduction - Rachel Atkinson; Sayby Berru; Laura Delgado; Fredy Yovera; James Berru; Yeny Robledo; Gaston Cruz (Food Additives & Contaminants: Part A, 2023)

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

‘From soil to chocolate bar’: identifying critical steps in the journey of cadmium in a Colombian cacao plantation - Daniel Bravo; Margareth Santander; Jader Rodríguez; Sebastian Escobar; Gideon Ramtahal; Rachel Atkinson (Food Additives & Contaminants: Part A, 2022)

Effects of the cannabinoid receptor agonist CP-55,940 on incentive salience attribution - Ali Gheidi; Lora M. Cope; Christopher J. Fitzpatrick; Benjamin N. Froehlich; Rachel Atkinson; Coltrane K. Groves; Clair N. Barcelo; Jonathan D. Morrow (Psychopharmacology, 2020)

Mapping tree species vulnerability to multiple threats as a guide to restoration and conservation of tropical dry forests - Tobias Fremout; Evert Thomas; Hannes Gaisberger; Koenraad Van Meerbeek; Jannes Muenchow; Siebe Briers; Claudia E. Gutierrez‐Miranda; José L. Marcelo‐Peña; Roeland Kindt; Rachel Atkinson; Omar Cabrera; Carlos I. Espinosa; et al. (Global Change Biology, 2020)
Understanding the vulnerability of tree species to anthropogenic threats is important for the efficient planning of restoration and conservation efforts. We quantified and compared the effects of future climate change and four current threats (fire, habitat conversion, overgrazing and overexploitation) on the 50 most common tree species of the tropical dry forests of northwestern Peru and southern Ecuador. We used an ensemble modelling approach to predict species distribution ranges, employed freely accessible spatial datasets to map threat exposures, and developed a trait‐based scoring approach to estimate species‐specific sensitivities, using differentiated trait weights in accordance with their expected importance in determining species sensitivities to specific threats. Species‐specific vulnerability maps were constructed from the product of the exposure maps and the sensitivity estimates. We found that all 50 species face considerable threats, with an average of 46% of species’ distribution ranges displaying high or very high vulnerability to at least one of the five threats. Our results suggest that current levels of habitat conversion, overexploitation and overgrazing pose larger threats to most of the studied species than climate change. We present a spatially explicit planning strategy for species‐specific restoration and conservation actions, proposing management interventions to focus on (a) in situ conservation of tree populations and seed collection for tree planting activities in areas with low vulnerability to climate change and current threats; (b) ex situ conservation or translocation of populations in areas with high climate change vulnerability; and (c) active planting or assisted regeneration in areas under high current threat vulnerability but low climate change vulnerability, provided that interventions are in place to lower threat pressure. We provide an online, user‐friendly tool to visualize both the vulnerability maps and the maps indicating priority restoration and conservation actions.

The development of visually guided stepping - Rachel Mowbray; Janna M. Gottwald; Manfei Zhao; Anthony P. Atkinson; Dorothy Cowie (Experimental Brain Research, 2019)

Epidemiological risk factors associated with inflammatory breast cancer subtypes - Rachel L. Atkinson; Randa El-Zein; Vicente Valero; Anthony Lucci; Therese B. Bevers; Tamer Fouad; Weiqin Liao; Naoto T. Ueno; Wendy A. Woodward; Abenaa M. Brewster (Cancer Causes & Control, 2016)

Feeding rates and prey selectivity of planktonic decapod larvae in the Western English Channel - Elaine S. Fileman; Penelope K. Lindeque; Rachel A. Harmer; Claudia Halsband; Angus Atkinson (Marine Biology, 2014)

Erratum to: The association of active smoking with multiple cancers: national census-cancer registry cohorts with quantitative bias analysis - Tony Blakely; Jan J. Barendregt; Rachel H. Foster; Sarah Hill; June Atkinson; Diana Sarfati; Richard Edwards (Cancer Causes & Control, 2014)

Eradicating multiple invasive species on inhabited islands: the next big step in island restoration? - Alistair S. Glen; Rachel Atkinson; Karl J. Campbell; Erin Hagen; Nick D. Holmes; Bradford S. Keitt; John P. Parkes; Alan Saunders; John Sawyer; Hernán Torres (Biological Invasions, 2013)

Identification of a possible respiratory arsenate reductase in Denitrovibrio acetiphilus, a member of the phylum Deferribacteres - Kyle Denton; Morgan M. Atkinson; Stacey P. Borenstein; Alexis Carlson; Thomas Carroll; Kristen Cullity; Casey DeMarsico; Daniel Ellowitz; Andrea Gialtouridis; Rachel Gore; April Herleikson; Albee Yun Ling; et al. (Archives of Microbiology, 2013)

The association of active smoking with multiple cancers: national census-cancer registry cohorts with quantitative bias analysis - Tony Blakely; Jan J. Barendregt; Rachel H. Foster; Sarah Hill; June Atkinson; Diana Sarfati; Richard Edwards (Cancer Causes & Control, 2013)

Residence time and human-mediated propagule pressure at work in the alien flora of Galapagos - Mandy Trueman; Rachel Atkinson; Anne Guézou; Penny Wurm (Biological Invasions, 2010)

Evidence for widespread cryptic sexual generations in apparently purely asexual Andricus gallwasps - GRAHAM N. STONE; RACHEL J. ATKINSON; ANTONIS ROKAS; JOSÉ‐LUIS NIEVES ALDREY; GEORGE MELIKA; ZOLTAN Ács; GYÖRGY CSÓKA; ALEXANDER HAYWARD; RICHARD BAILEY; CAROLINE BUCKEE; GILEAN A. T. McVEAN (Molecular Ecology, 2008)
Oak gallwasps (Hymenoptera, Cynipidae, Cynipini) are one of seven major animal taxa that commonly reproduce by cyclical parthenogenesis (CP). A major question in research on CP taxa is the frequency with which lineages lose their sexual generations, and diversify as purely asexual radiations. Most oak gallwasp species are only known from an asexual generation, and secondary loss of sex has been conclusively demonstrated in several species, particularly members of the holarctic genus Andricus. This raises the possibility of widespread secondary loss of sex in the Cynipini, and of diversification within purely parthenogenetic lineages. We use two approaches based on analyses of allele frequency data to test for cryptic sexual generations in eight apparently asexual European species distributed through a major western palaearctic lineage of the gallwasp genus Andricus . All species showing adequate levels of polymorphism (7/8) showed signatures of sex compatible with cyclical parthenogenesis. We also use DNA sequence data to test the hypothesis that ignorance of these sexual generations (despite extensive study on this group) results from failure to discriminate among known but morphologically indistinguishable sexual generations. This hypothesis is supported: 35 sequences attributed by leading cynipid taxonomists to a single sexual adult morphospecies, Andricus burgundus, were found to represent the sexual generations of at least six Andricus species. We confirm cryptic sexual generations in a total of 11 Andricus species, suggesting that secondary loss of sex is rare in Andricus .

Neurocognitive Effects of Methamphetamine: A Critical Review and Meta-analysis - J. Cobb Scott; Steven Paul Woods; Georg E. Matt; Rachel A. Meyer; Robert K. Heaton; J. Hampton Atkinson; Igor Grant (Neuropsychology Review, 2007)

The phylogeographical clade trade: tracing the impact of human‐mediated dispersal on the colonization of northern Europe by the oak gallwasp Andricus kollari - GRAHAM N. STONE; RICHARD J. CHALLIS; RACHEL J. ATKINSON; GYÖRGY CSÓKA; ALEX HAYWARD; GEORGE MELIKA; SERAP MUTUN; SONJA PREUSS; ANTONIS ROKAS; EBRAHIM SADEGHI; KARSTEN SCHÖNROGGE (Molecular Ecology, 2007)
Human dispersal of organisms is an important process modifying natural patterns of biodiversity. Such dispersal generates new patterns of genetic diversity that overlie natural phylogeographical signatures, allowing discrimination between alternative dispersal mechanisms. Here we use allele frequency and DNA sequence data to distinguish between alternative scenarios (unassisted range expansion and long range introduction) for the colonization of northern Europe by an oak‐feeding gallwasp, Andricus kollari . Native to Mediterranean latitudes from Portugal to Iran, this species became established in northern Europe following human introduction of a host plant, the Turkey oak Quercus cerris . Colonization of northern Europe is possible through three alternative routes: (i) unassisted range expansion from natural populations in the Iberian Peninsula; (ii) unassisted range expansion from natural populations in Italy and Hungary; or (iii) descent from populations imported to the UK as trade goods from the eastern Mediterranean in the 1830s. We show that while populations in France were colonized from sources in Italy and Hungary, populations in the UK and neighbouring parts of coastal northern Europe encompass allozyme and sequence variation absent from the known native range. Further, these populations show demographic signatures expected for large stable populations, rather than signatures of rapid population growth from small numbers of founders. The extent and spatial distribution of genetic diversity in the UK suggests that these A. kollari populations are derived from introductions of large numbers of individuals from each of two genetically divergent centres of diversity in the eastern Mediterranean. The strong spatial patterning in genetic diversity observed between different regions of northern Europe, and between sites in the UK, is compatible with leptokurtic models of population establishment.

Out of Anatolia: longitudinal gradients in genetic diversity support an eastern origin for a circum‐Mediterranean oak gallwasp Andricus quercustozae - Antonis Rokas; Rachel J. Atkinson; Lucy Webster; György Csóka; Graham N. Stone (Molecular Ecology, 2003)
Many studies have addressed the latitudinal gradients in intraspecific genetic diversity of European taxa generated during postglacial range expansion from southern refugia. Although Asia Minor is known to be a centre of diversity for many taxa, relatively few studies have considered its potential role as a Pleistocene refugium or a potential source for more ancient westward range expansion into Europe. Here we address these issues for an oak gallwasp, Andricus quercustozae (Hymenoptera: Cynipidae), whose distribution extends from Morocco along the northern coast of the Mediterranean through Turkey to Iran. We use sequence data for a fragment of the mitochondrial gene cytochrome b and allele frequency data for 12 polymorphic allozyme loci to answer the following questions: (1) which regions represent current centres of genetic diversity for A. quercustozae ? Do eastern populations represent one refuge or several discrete glacial refugia? (2) Can we infer the timescale and sequence of the colonization processes linking current centres of diversity? Our results suggest that A. quercustozae was present in five distinct refugia (Iberia, Italy, the Balkans, southwestern Turkey and northeastern Turkey) with recent genetic exchange between Italy and Hungary. Genetic diversity is greatest in the Turkish refugia, suggesting that European populations are either (a) derived from Asia Minor, or (b) subject to more frequent population bottlenecks. Although Iberian populations show the lowest diversity for putatively selectively neutral markers, they have colonized a new oak host and represent a genetically and biologically discrete entity within the species.

Differential success in northwards range expansion between ecotypes of the marble gallwasp Andricus kollari : a tale of two lifecycles - Graham Stone; Rachel Atkinson; Antonis Rokas; György Csóka; José‐Luis Nieves‐Aldrey (Molecular Ecology, 2001)
The Marble gallwasp Andricus kollari has a native range divided into two geographically separated lifecycles. In Eastern Europe and Turkey, the lifecycle involves a sexual generation on Turkey oak, Quercus cerris , while in Iberia and North Africa the sexual generation host is cork oak, Q. suber . Over the last 500 years, A. kollari has expanded its range into northern Europe, following human planting of Q. cerris from Italy and the Balkans. We ask: (i) what is the genetic relationship between eastern and western distributions of Andricus kollari ? Can we determine which lifecycle is ancestral, and how long ago they diverged? (ii) To what extent have eastern and western native ranges contributed to northwards range expansion? (iii) Is there any evidence for hybridization between the two life cycle types? We present analyses of allozyme data for 13 polymorphic loci and of sequence variation for a 433 bp fragment of the mitochondrial cytochrome b gene. These show: (i) that four haplotype lineages (one in Spain, two in Hungary/Italy and one in Turkey) diverged more or less simultaneously between 1 and 2 million years ago, suggesting the existence of at least four refuges through recent ice age cycles. Our data cannot resolve which lifecycle type is ancestral. (ii) Populations north of putative refuges are divided into two sets. Populations in south‐west France are allied to Spain, while all remaining populations in northern Europe have been colonized from Italy and the Balkans. (iii) The transition from one race to another in south‐west France is marked by abrupt transitions in the frequency of refuge‐specific private alleles and corresponds closely to the northern limit of the distribution of cork oak. Although hybrids were detected in north‐west France, none were detected where the two lifecycles meet in south‐western France. The biology of oak gallwasps predicts that any hybrid zone will be narrow, and limited to regions where Q. cerris and Q. suber meet. Our data suggest that eastern and western A. kollari are effectively separate species.